Respuestas

  • Usuario de Brainly
2012-10-18T00:49:48+02:00

x=(1-5y)/6                                4x+6(.5)=2

4((1-5y)/6)=2-6y                       4x+3=2

(4-20y)/6=2-6y                         4x=-1

4-20y=12-36y                             x=-1/4

36y-20y=12-4                             x= -0.25

16y=8                                       

y=8/16

y= 0.5

 

2012-10-18T01:05:43+02:00

4X + 6Y = 2                                           6x + 5y = 1                                                     X = 2 – 6y                                            6X  = 1 – 5y

                  2 – 6y                                          1 – 5Y

       X =     =====                                 X = ========

                    4                                                    6

Igualo

                 2 – 6y           1 – 5Y

                 =====   =   ========

                    4                    6                                              

                                                                                         

6 * (2 – 6y ) = 4 * (1 – 5Y )                                          despejo X

12 – 12Y = 4 – 20 Y                                                            2 – 6y  

-12 Y + 20 Y = 4 – 12                                               X =     =====                                 

              8 Y = -8                                                                4                                                    

               Y = - 8 / 8                                             2 – 6 * -1          2 + 6       8

               Y = -1                                            X = ========== = ====== = ======  = 2

                                                                           4                      4           4

 

     prueba   

    4X + 6Y = 2                                                                                                                     X = 2

    4 * 2 + 6 * -1 = 2

        8 – 6 = 2

             2 = 2